Stereotactic radiofrequency ablation (SRFA) for recurrent colorectal liver metastases after hepatic resection. Issue 4 (April 2021) - Schullian, Peter; Johnston, Edward W.; Putzer, Daniel; Laimer, Gregor; Waroschitz, Gregor; Braunwarth, Eva; Amann, Arno; Maglione, Manuel; Bale, Reto
Abstract: Background: To evaluate the efficacy, safety and overall clinical outcome of multiprobe SRFA as a treatment for recurrent colorectal liver metastases after hepatic resection (HR). Methods: A retrospective, single center study carried out between 2006 and 2018. 64 consecutive patients with recurrent or new CRLM after previous HR were treated by SRFA for 217 lesions (median size 2.7 cm, 1–7.5) in 103 ablation sessions. Endpoints consisted of i) technical efficacy ii) complication and mortality rates iii) local and distant recurrence, iv) disease free survival (DFS), and v) overall survival (OS). Results: 213/217 tumors were successfully ablated at initial SRFA (97.7% primary technical efficacy rate). Four tumors required repeat ablation, resulting in a secondary technical efficacy rate of 99.5% (216/217). Local recurrence developed in 25/217 lesions (11.5%). Major complication rate was 5.8% (6/103 sessions) and mortality rate was 1.0% (1/103 ablation sessions), respectively.1-, 3-, and 5- year OS rates from date of first SRFA were 90.1%, 46.2%, and 34.8% (median 33.1 months). DFS rates were 54.2%, 17.2%, and 17.2%, at 1-, 3- and 5- years, respectively (median 13.3 months). Conclusion: SRFA is a safe, feasible and effective option for CRLM after HR with low morbidity levels and favorable clinical outcome.